Book review: Pulk, Kätlin and Koris, Riina (Eds.). Generative AI in higher education. The good, the bad, and the ugly - Wilson, Thomas (Information Research an international electronic journal, 2025)
Pulk, Kätlin and Koris, Riina (Eds.). (2025). Generative AI in higher education. The good, the bad, and the ugly. Edward Elgar. 2025. 214 p. ISBN: 9781035326013